Impact of practice-centered learning on the development of students’ professional identities: Learning outcomes - Knissarina, Malika; Syzdykbayeva, Aigul; Agranovich, Yelena; Zhumaliyeva, Gulmira; Baikulova, Aigerim (Journal of Education and e-Learning Research, 2024)
The progress of education in our country is still constrained by the low status of teaching. The comprehension and growth of university students’ stages of professional identity creation are not well researched. This issue is now recognized on both a theoretical and practical level. This research aimed to examine the effectiveness of providing practice-centered learning in the construction of students’ professional identities. The study employed a mixed-data collection strategy. A random sample of respondents was used to generate quantitative data. The study involved 253 learners at "Baishev University," Aktobe, Kazakhstan. According to the study’s findings, low levels of development have been found in students’ professional identity, motivation and interest in professional self-development. This demonstrated the importance of resource support for educational innovations as well as the development and implementation of technology-based practice-centered learning for future teachers. As a result of evaluating the implementation of technology-based practice-centered learning and resource support for educational innovations, positive dynamics shaping learners’ professional identities are identified. Thus, the study’s findings confirmed our hypothesis that using practice-centered learning to foster students’ professional identities has a positive impact when systemic and technological approaches are used.